2020
DOI: 10.3767/persoonia.2020.44.03
|View full text |Cite
|
Sign up to set email alerts
|

A new species concept for the clinically relevant Mucor circinelloides complex

Abstract: Mucor species are common soil fungi but also known as agents of human infections (mucormycosis) and used in food production and biotechnology. Mucor circinelloides is the Mucor species that is most frequently isolated from clinical sources. The taxonomy of Mucor circinelloides and its close relatives (Mucor circinelloides complex – MCC) is still based on morphology and mating behaviour. The aim of the present study was a revised taxonomy of the MCC using a polyphasic approach. Using a set of 100 strains molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 80 publications
6
80
0
1
Order By: Relevance
“…The main results of our study are the species-specific AFS profiles of opportunistic Mucor species based on the revised taxonomy, which further support the recent taxonomic revision (6) (6), exhibited different AFS profiles. Mucor lusitanicus showed high MIC values for all azoles tested.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The main results of our study are the species-specific AFS profiles of opportunistic Mucor species based on the revised taxonomy, which further support the recent taxonomic revision (6) (6), exhibited different AFS profiles. Mucor lusitanicus showed high MIC values for all azoles tested.…”
Section: Discussionsupporting
confidence: 83%
“…Molecular species identification based on internal transcribed spacer (ITS) sequences (see Table S1 in the supplemental material) was unambiguous for all strains studied. ITS sequences of strains that were not identified in former taxonomic studies (6,40) showed ITS sequence similarities of Ն99% with the respective ex-type strains.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations